Climate Change and the Role of Agricultural Extension in Adaptation and Mitigation: A Review Article - Mahmood, Ekhlas Thaer (American Journal of Biodiversity, 2025)
Global agriculture is facing escalating challenges due to climate change, which exerts profound impacts on crop productivity and natural resource availability, necessitating the implementation of effective adaptation strategies. This review examines the role of agricultural extension in empowering farmers to navigate these climatic shifts. As a critical conduit between scientific research and practical application, agricultural extension plays a pivotal role in disseminating innovative technologies and sustainable agricultural practices. The study delves into the implications of rising temperatures, shifting precipitation regimes, and the heightened frequency of extreme weather events on agricultural systems. It further analyzes how agricultural extension services facilitate farmers’ adaptation by providing technical support and capacity-building initiatives through workshops, training programs, digital applications, and advanced information systems. Additionally, the study underscores the significance of local and global collaboration among governmental bodies, research institutions, and non-governmental organizations (NGOs) to foster knowledge exchange and develop robust adaptation frameworks. The incorporation of circular economy models, which advocate for agricultural waste recycling, efficient soil and water resource management, is also highlighted as a fundamental strategy for promoting agricultural sustainability. Findings emphasize that investment in the continuous professional development of agricultural extension agents and the modernization of digital infrastructure constitutes a cornerstone for enhancing the efficacy of extension programs in mitigating climate-related challenges. Moreover, the study explores the transformative potential of emerging technologies, including artificial intelligence (AI), big data analytics, and predictive modeling, in refining climate forecasting and delivering precision-driven agricultural recommendations. In light of these insights, the study advocates for increased financial investment in agricultural extension, the alignment of agricultural and climate policies, and the expansion of community-based support networks. Such measures are instrumental in fostering long-term food security and ensuring the resilience and sustainability of agricultural systems in the face of climate variability.